An investigation of physical processes in nanosphere lithography - Agam, Mohd Arif (2006)
Various physical processes have been investigated in order to improve the Nanosphere Lithography (NSL) technique by modifying the nanosphere structures. Polysytrene CPS) nanospheres used in NSL can be modified in three schemes: Electron beam, heat and chemical manipulation techniques. The most successful scheme to modify nanosphere structures is by the electron beam manipulation technique. Using electron beam irradiation, both the size and shape of the nanospheres can be modified in a controlled manner. An ordered array of spheres can be modified by electron beam irradiation to create a pattern otherwise not available through selfassembly alone. Mechanisms of polymer degradation induced by energetic electrons are discussed. Heat and chemical manipulation techniques have created freestanding transportable nanospheres thin films (FTNFs) that can be further processed with reactive ion etching (RIE) to create a freestanding transportable lithography mask. A unique honeycomb structure has been created when PS nanospheres were treated with organic solvents. The formation of the honeycomb structure depends on the concentration of the organic solvents and the nanosphere dissolution rate when in contact with organic solvents.